Synthesis of activity evaluation of flavonoid derivatives as ɑ-glucosidase inhibitors - Zhu, Hua; Zhong, Xin (Frontiers in Chemistry, 2022)
Six flavonoid derivatives were synthesized and tested for anti-α-glucosidase activities. All derivatives were confirmed using NMR and HRMS and exhibited excellent inhibitory effects on α-glucosidase. Derivative four exhibited the highest anti-α-glucosidase activity (IC50: 15.71 ± 0.21 μM). Structure-activity relationship results showed that bromine group would be the most beneficial group to anti-α-glucosidase activity. Inhibitory mechnism and inhibition kinetics results showed derivative four was a reversible and mixed-type inhibitor. Molecular docking revealed that derivative four was tightly bind to the amino acid residues of active pocket of α-glucosidase and formed hydrogen bond, π-π stacking, and Pi-Donor hydrogen with α-glucosidase. Moreover, the physicochemical parameters of all derivatives were assessed using SwissADME software. This results also showed that the hybridization of flavonoid and phenylpropionic acid would be a useful strategy for the development of α-glucosidase inhibitors.